Phylogenetic relationships of megophryid frogs of the genus Leptobrachium (Amphibia, Anura) as revealed by mtDNA gene sequences - Matsui, M.; Hamidy, A.; Murphy, R.W.; Khonsue, W.; Yambun, P.; Shimada, T.; Ahmad, N.; Belabut, D.M.; Jiang, Jian-Ping (Elsevier, 2010)
By investigating genealogical relationships, we estimated the phylogenetic history and biogeography in the megophryid genus Leptobrachium (sensu lato, including Vibrissaphora) from southern China, Indochina, Thailand and the Sundaland. The genealogical relationships among the 30 named and unnamed taxa were estimated using 2009 bp of sequences from the mitochondrial DNA genes 12S rRNA, tRNA(val), and 16S rRNA using maximum parsimony, maximum likelihood, and Bayesian inference methods. The genus Leptobrachium was a well-supported monophyletic group that contained two major clades. One clade had three subclades primarily from disjunct regions including Borneo, Peninsular Malaysia and Java, and Thailand. The Bornean subclade included one species each from the Philippines and Sumatra. The other major clade consisted of two subclades, one from Indochina and the other from southern China (Vibrissaphora). Divergence times estimated an old evolutionary history of each subclade, one that could not be explained by the geohistory of Southeast Asian major landmasses. (C) 2010 Elsevier Inc. All rights reserved.